Child Nutrition Among Circular Migrant Families Working in the Brick Kilns of Bihar, India (P10-052-19). (13th June 2019) - Roshania, Reshma; Giri, Rakesh; Young, Melissa Fox; Mala, G Sai; Girard, Amy Webb; Cunningham, Solveig Argeseanu; Das, Aritra; Mahapatra, Tanmay; Srikantiah, Sridhar; Ramakrishnan, Usha
Abstract: Objectives: The objective of this study was to estimate the prevalence of child malnutrition and the determinants of nutrition status among circular migrant families working in the brick industry in Bihar, India, focusing on differences by origin. Methods: We used a stratified, cluster sampling design consisting of a cross-sectional survey in 552 randomly selected brick kilns (clusters) throughout Bihar. Circular migration was defined as residence outside the home block for at least 60 days for employment plus at least one home return in the previous year. Per kiln, three circular migrant households with children 0–35 months of age were randomly selected. We collected kiln, household and child-level data including anthropometric measurements for each selected child ( n = 1198). Descriptive, bivariate and logistic regression analyses were conducted in SAS. The primary outcomes were stunting (<-2 SD height-for-age z score) and wasting (<-2 SD weight-for-height z score). The primary exposure of interest was intrastate vs. interstate origin; covariates included household wealth index, parity of the mother, and child age and gender. Results: Prevalence of stunting was lower among interstate migrants (47%) compared to intrastate migrants (55%, aOR: 0.66, 95%CI: 0.50–0.88). Wasting was higher among interstate migrants (43%) compared to intrastate migrants (34%, aOR:1.51, 95%CI: 1.17–1.94). Among children 6–23 months, 13% had a minimum acceptable diet; MAD was higher among interstate migrants (17%), compared to intrastate migrants (10%) ( P = 0.014). Full immunization coverage among circular migrants was 39%, lower than the overall state (62%, NFHS IV). Open defecation was reported by over 90% of circular migrants. Conclusions: Our results are likely to inform the ongoing policy discourse on circular migrants' access to health and nutrition benefits. State of origin emerged as an important predictor of nutrition status, operating differently for acute and chronic malnutrition; we will further explore pathways of nutrition by origin in future analyses. Funding Sources: Bill & Melinda Gates Foundation.